Diversity, potentiality, and conservation status of fish fauna in the upper Mahakam’s tributaries, East Kalimantan - Jusmaldi Jusmaldi; Nova Hariani; Norbeta Doq (Jurnal Iktiologi Indonesia, 2019)
Diversity, potentiality and conservation status of fish fauna in upper Mahakam’s tributaries of east Kalimantan is unknown. The purposes of this study were to analysis species diversity, determine potentiality and conservation status of fish fauna in upper Mahakam’s tributaries, east Kalimantan. Fish sampling with purposive method was conducted in four tributaries, i.e Tepai River, Pahangai River, Danum Parai River, and Meraseh River for one month. Fishes were collected by several gears type. The results of this research showed that the total number of fish caught was 820 individuals; consist of 26 species, 7 families, and 4 orders. The Cyprinidae was the most dominant family found in all tributaries. The Shannon-Wiener diversity index in four tributaries were varied and ranging from 1.749-2.087. The highest fish diversity was recorded at Maraseh River followed by Pahangai River, Danum Parai River, and Tepai River. The low fish diversity was discovered at Tepai River may be due to differences in substrate type, water velocity, and water depth as compared to the Maraseh River, Pahangai River, Danum Parai River. The fish species similarity coefficient between four tributaries ranged from 0.606-0.842 and the highest dissimilarity was found between Tepai River and Danum Parai River. Almost all fishes categorized as edible fish for local consumption. Syncrossus hymenophysa and Gastromyzon lepidogaster have potential as ornamental fish. Regarding IUCN red list status, six fish species were grouped into least concern status, two species as data deficient, one species as near threatened, one species as endangered species and 16 other species were not on the list. Abstrak Keanekaragaman, potensi, dan status konservasi fauna ikan di anak Sungai Mahakam Hulu, Kalimantan Timur belum diketahui. Tujuan penelitian ini adalah mengungkap tingkat keanekaragaman spesies dan mengidentifikasi potensi serta status konservasi fauna ikan di anak Sungai Mahakam hulu, Kalimantan Timur. Pengambilan contoh ikan dila-kukan di empat anak sungai, meliputi Sungai Tepai, Sungai Pahangai, Sungai Danum Parai, dan Sungai Meraseh sela-ma satu bulan dengan menggunakan berbagai alat tangkap. Hasil penelitian menunjukkan total ikan yang tertangkap sebanyak 820 individu, terdiri atas 26 spesies, 7 famili, dan 4 ordo. Famili Cyprinidae adalah paling dominan ditemu-kan di semua anak sungai. Indeks keanekaragaman Shannon-Wiener pada empat anak sungai bervariasi dan berkisar antara 1,749-2,087. Keanekaragaman ikan tertinggi tercatat di Sungai Maraseh diikuti oleh Sungai Pahangai, Sungai Danum Parai, dan Sungai Tepai. Keanekaragaman ikan terendah di Sungai Tepai diduga disebabkan oleh perbedaan tipe substrat, kecepatan air, dan kedalaman air dibandingkan dengan Sungai Maraseh, Sungai Pahangai, Sungai Da-num Parai. Koefisien kesamaan spesies ikan antar empat anak sungai berkisar 0,606–0,842 dan terendah ditemukan antara Sungai Tepai dan Sungai Danum Parai. Sebagian besar spesies ikan dimanfaatkan oleh masyarakat lokal se-bagai ikan konsumsi. Spesies Syncrossus hymenophysa dan Gastromyzon lepidogaster berpotensi sebagai ikan hias. Berdasarkan status daftar merah IUCN ditemukan enam spesies berisiko rendah, dua spesies kurang data, satu spesies hampir terancam, satu spesies terancam dan sebanyak 16 spesies tidak ditemukan dalam daftar.